Factores de riesgos asociados a la desnutrición en niños de 1-5 años de la unidad operativa de salud “Centro Urbano Vinces”, Los Ríos, diciembre 2022-mayo 2023. - Chávez Guapulema, Lidia Nicole (2023)
Globally, one in three children under five years of age is stunted because they suffer from one of the most well-known forms of malnutrition, including overweight, wasting and stunting. For this reason, the research has set the objective of evaluating the risk factors associated with malnutrition in children between 1 and 5 years of age of the “Centro Urbano Vinces” Health Operations Unit, Los Ríos province, December 2022- May 2023. Its methodology It is of an inductive-deductive nature, of a descriptive, correlational, and quantitative nature. His sample corresponded to 60 children from 1 to 5 years of age cared for in the Vinces Urban Center. For the data collection, the survey with questions corresponding to the study variables was applied as a technique. The results of the investigation showed that the children present height, weight and BMI, in normal values, however, there were children with severe thinness, obesity and overweight; Among the risk factors, the schooling of the mothers, economic income, marital status, type of diet, number of children and the sector where they live, which predominated in rural areas, stood out. It is concluded that risk factors affect malnutrition in children, with a high significant correlation (p=0.798). A proposal focused on training mothers on healthy eating was raised.